STUDENTS’ SPEAKING PERFORMANCE ANALYSIS AFTER LEARNING USING GOOGLE MEET AT PANDEMIC ( COVID 19) ERA - Ernati Ernati; Lesina Merti (Universitas Bung Hatta, 2022)
The aim of this research is to find out the first year students’ speaking performance after learning using google meet at Pandemic (Covid 19). There are 30 students chosen totally as the object of this research. Speaking test is used to know the students’ speaking performance. The result showed that the first year students’ speaking performance after learning using Google is excellent. Their performance in expressing idea (content), in pronunciation, in vocabulary is excellent. Somehow, their performance in grammar and fluency are good (not excellent/ optimal). It is recommended that the speaking subject lecturer give many opportunities for students to improve student’s capability in grammar and fluency through practicing much in sentence construction and in releasing their hesitation in speaking in daily communication. They are influenced by native language frame and nervous when they are speaking. The students are suggested to keep their ability excellent in speaking skill, but they should improve their ability in the aspect of speaking such as grammar and fluency. For the next researcher is recommended to find out the causes of the students’ speaking performance in grammar and fluency is good (not excellent). REFERENCES Afifah, Sihatul. (2016). Analysis Students’ Speaking Skill Based on Local Material At First Semester in English Department of UNSWAGATI. Jurnal Pendidikan Bahasa Inggris. Vol 4, No 2. Page 96 Afnah, Mauloeddin. (2018). The Correlation Between Vocabulary and Speaking Skill. Journal of Linguistics, Literature & Language Teaching. Vol 4, No 1. Page 67 Arikunto, S (2012). Dasar-Dasar Evaluasi Pendidikan. Jakarta: PT. Bumi Akasara. Arikunto, S. (2015). Penelitian Tindakan Kelas. Jakarta: Bumi Aksara. Brown, H. Douglas and Priyanvada Abeywickrama. (2010). Language Assessment Principle and Classroom Practice. New York: Pearson Education, Inc. Carmen, Robert. (2010). Spoken English: Flourish Your Language. Chandigarh: Abhishek Publications. Gay, L.R. (2009). Educational Research: Competencies for Analysis and Application (9th Ed). New Jersey: Merrill Publishing Company. Harmer, Jeremy. (2001). How To Teach English: An Intriduction To The Practice Of English Language Teaching. England: Pearson Education Limited. Hartiwi, Juni, Herpratiwi and Sudirman. (2013). Peningkatan Keterampilan Berbicara Bahasa Inggris. Jurnal Teknologi Informasi Komunikasi Pendidikan. Vol 1, No 2. Hendriani, Suswati and Nina Suzanne. (2013). Language Testing. Batusangkar: STAIN Batusangkar Express. Juniartini & Rasna. (2020). Pemanfaatan Aplikasi Google Meet Dalam Keterampilan Menyimak Dan Berbicara Untuk Pembelajaran Bahasa Pada Masa Pandemi Covid-19. Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia. Vol 9, No 2. Page 2 Leo, Sutanto. (2013). A Challenging Book to Practice Teaching in English. Yogyakarta: C.V Andi Offset. Leong, Lai Mei & Seyedeh Masoumeh Ahmadi. (2017). An Analysis of Factors Influencing Learners’ English Speaking Skill. International Journal of Research in English Education. Vol 2, No 1. Page 36 Mairi, Sudirman, & Budiarta. (2017). An Analysis of Speaking Fluency Level of The Sixth Semester Students of English Language Education Department in Ganesha University of Education (UNDIKSHA). Jurnal Pendidikan Bahasa Inggris. Vol 5, No 2. Page 8 Mishra, Shanti Bushan and Shashi Alok. (2011). Handbook of Research Methodology. New Delhi: Educreation Publishing. Nunan, David. (2003). Practical English Language Teaching. New York: McGraw-Hill Companies, Inc. Prawiradilaga, Dewi Salma. (2012) Wawasan Teknologi Pendidikan. Jakarta: Kencana Prenada Media Group: 277 Refnita, L. (2018). Educational Research: A Guide For Beginners. Padang: LPPM Universitas Bung Hatta. Sari, Refa Anjeng. (2018). Students’ Grammatical Error Analysis in Speaking. Jurnal Pendidikan dan Pengajaran. Vol 5, No 2. Page 132 Siregar, Syahreni (2017). The Influence of Dialect on The Students’ Pronunciation in Speaking Ability. Journal of English Language Teaching. Vol 5, No 1. Page 35 Sawitri, Dara. (2020). Penggunaan Google Meet untuk Work From Home di Era Pandemi Coronavirus Disease 2019 (Covid-19). Jurnal Pengabdian Masyarakat. Vol 2, No 14. Page 13-19 Thornbury, Scott. (2005). How To Teach Speaking. Harlow: Pearson Education Limited.